2022
DOI: 10.1039/d2dt02307e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and reactivity of dinuclear copper(i) pyridine diimine complexes

Abstract: The reaction of a tethered pyridine diimine (PDI) ligand with copper(I) chloride yielded a µ-chlorido bridged cationic dicopper(I) PDI complex, which is a rare structural motif. The geometric constriction of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…They concluded that the local force constants they observed for their complexes fell inline with the lowest calculated dissociation energies for the bonding interactions, and deduced these models provided congruent characterizations for the model chemistry. Burger and his group were able to confirm the weak interactions between binuclear copper­(I) pyridine diimine centers when comparing the local force constants to the Mayer bond order and Wiberg and Fuzzy Cu–Cu bond orders. They also recently applied LMA in a study on the rare cleavage of an aromatic C–C bond in ferrocene by insertion of an iridium nitrido nitrogen atom.…”
Section: Resultsmentioning
confidence: 98%
“…They concluded that the local force constants they observed for their complexes fell inline with the lowest calculated dissociation energies for the bonding interactions, and deduced these models provided congruent characterizations for the model chemistry. Burger and his group were able to confirm the weak interactions between binuclear copper­(I) pyridine diimine centers when comparing the local force constants to the Mayer bond order and Wiberg and Fuzzy Cu–Cu bond orders. They also recently applied LMA in a study on the rare cleavage of an aromatic C–C bond in ferrocene by insertion of an iridium nitrido nitrogen atom.…”
Section: Resultsmentioning
confidence: 98%
“…Tridentate pyridine di-imine NNN-donor ligands are ubiquitous and employed in main group and transition metal complexes, including both, mono-and dinuclear systems [27][28][29][30][31]. They are commonly prepared by the Schiff-base condensation of a 2,6-diketo or dialdehyde pyridine with two equivalents of a desired aniline or amine derivative [27,28].…”
Section: Synthesis Of Ligandmentioning
confidence: 99%